Detection of bovine herpes virus (BOHV-1) infection in respiratory tract of bovines - GANGIL, RAKHI; KAUR, GURPREET; DWIVEDI, P N (The Indian Journal of Animal Sciences, 2020)
Infectious bovine rhinotracheitis (IBR) is considered commonest form of BoHV-1 respiratory tract infection. The current work was designed to study the incidence of IBR using molecular technique and antigen detection sandwich ELISA. In the present study, nasal swab samples (100) and tracheal lavages (6) were collected from bovines, which were showing respiratory symptoms from clinics of College of Veterinary Science, GADVASU, Ludhiana. Four lung tissues were also collected from dead animals. All nasal samples were tested for IBR virus antigen by using commercial sandwich ELISA kit. The antigenic incidence of BoHV-1 was reported to be 1% in tested animals. For molecular detection of BoHV-1 in respiratory tract, the DNA was extracted from all samples (nasal swabs, tracheal lavages and lung tissues) and subjected to gI gene specific PCR by using published primers. The overall incidence of BoHV-1 in nasal swabs of animals with the history of respiratory symptoms was found to be 3% and rest of the samples were found negative for IBR virus in PCR. Species wise evaluation of BoHV-1 infection revealed that out of 75 cattle, 3 (4.0%) cattle were found positive in PCR where as none of the buffaloes were found positive in present study. The animals older than 3 year of age showed the higher incidence (4.2%) than animal up to 3 years of age (2.8%). In this study, all positive cattle were crossbred females. According to sex wise status, it was observed that females are more prone to infection, which may be because of production stress in female animals.